Seeing the invisible: a photovoice exploration of living with, and managing the invisible symptoms of Multiple Sclerosis - Parker, L. (2021)
Background: Multiple Sclerosis (MS) is a chronic inflammatory disease of the central nervous system, characterised by an abnormal immune system response which causes axonal demyelination. MS presents a range of debilitating cognitive, sensory, motor and affective symptoms. Some of the symptoms of MS are classified as ‘invisible’, due to the fact that they are not easily observable to others and are ‘hidden’. Common invisible symptoms include cognitive impairment, fatigue, pain, bladder and bowel dysfunction, sexual problems, and sensory dysfunction. Research shows that living with invisible symptoms causes distress for people with MS that differs from that of visible symptoms, not only because of their physical impacts, but because of their invisible nature. Studies highlight the issues associated with invisible symptoms, whereby people with MS do not feel understood or believed by others in relation to their invisible symptoms and attempt to navigate their difficulties brought about by this. There is a dearth of research offering in-depth exploration of lived experience of a cluster of invisible MS symptoms.